Processing and Utilization of Inorganic Waste into Economically Valuable Products - Elva Elfira; Surahmawati, Surahmawati; Amansyah, Munawir; Syarif, Alwiyah Nur (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
Waste management is a complex challenge faced globally, including Indonesia. This is due to the imbalance between waste production and processing. Waste production in Indonesia reaches around 23.1 million tons of waste every year. With high inorganic waste production, effective waste handling and processing efforts are needed to reduce excess waste volume. The purpose of this study is to assess the effectiveness of the counseling and training program for processing inorganic waste into crafts by measuring the increase in knowledge of SD Negeri Kanreapia students about processing inorganic waste into crafts and assessing the sustainability of processing inorganic waste into crafts. The type of evaluation conducted is using a mixed methods research approach, which is an approach that combines quantitative and qualitative methods with a total of 31 respondents. The quantitative method uses a questionnaire as a research instrument, while qualitative is done by observation and in-depth interviews. The evaluation results based on the Friedman test showed that there was a significant difference (p-value = 0.000 <0.05) in respondents' knowledge before, after training, and after 8 months of intervention with sufficient knowledge of 70.9% or 22 respondents. The results of the activity showed a significant difference in respondents' knowledge related to inorganic waste processing before the intervention, after the intervention, and after 8 months of intervention.